Strategies to Reduce the Level of Violence Against Women and Children in Surabaya City - Mita Destiana; Amirul Mustofa; Zaenal Fatah (International Journal Labs, 2023)
This study aims to evaluate the efforts made by the Department of Women's Empowerment and Child Protection (DWECP) in Surabaya City to reduce Violence against women and children. Members prioritize the selection of strategies and activities. When organizational members make decisions, they consider all aspects of the organization or its people. In this study, researchers used a qualitative approach, which was rewritten to become a scientific description. The methods used to find out the results include enabling, strengthening, protecting, enabling, and nurturing. The results show that several activities or efforts are made to reduce the level of Violence, such as counseling the community, providing healing strategies to individuals or families, and helping to resolve cases of Violence against women and children that have occurred and reported to the authorities. The results of these activities are significant and may impact reducing Violence against women and children. Can optimize all aspects and resources based on the selected activities and efforts.